Re-imagining Creative Music-making: Creative Music Series #8 - Attariwala, Parmela (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Within days of Vancouver locking down in March 2020, NOW Society’s artistic director, Dr. Lisa Cay Miller, crafted an imaginative means of engaging local and international improvisers in an online series, Creative Music Series #8 (CMS#8). The series showcased not only the musicians’ improvisatory skills, but their compositional abilities. Drawing upon conversations with musicians who took part in CMS#8, Parmela Attariwala reflects upon how the series shaped the early days of the COVID-19 pandemic for her and fellow improvisors involved in the series. She also considers the artistic potency enabled by the mode of creation developed for CMS#8.